PENGARUH TRANSAKSI NON TUNAI TERHADAP JUMLAH UANG BEREDAR DI INDONESIA TAHUN 2019-2021 DENGAN INFLASI SEBAGAI VARIABEL MODERASI - shinta ainur rahmadani; aprika wanti pratama; nurma yunita; Maya Panorama (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2022)
Non-cash transactions in monetary policy affect the level of money circulating in society. In addition, another factor that affects the amount of money in circulation is inflation. Non-cash transactions in this study use Debt APMK, Credit APMK, and electronic money (e-money). The purpose of this study was to determine the effect of non-cash transactions on the money supply in Indonesia with inflation as a moderating variable during 2019-2021. The research uses secondary data and the analysis technique used is multiple linear regression analysis and the Moderating Regression Analysis (MRA) test. The results of the study state that non-cash transactions have a partially and simultaneously significant effect on the money supply and inflation is able to strengthen the relationship of non-cash transactions on the money supply.